Corrosion-resistant steel strip and preparation method thereof
By using an electroless plating solution and a plasma glow nitriding furnace for the preparation of corrosion-resistant steel strips, combined with the casting and rolling of alloy powder, the problem of easy cracking of the anti-rust coating of the steel strip is solved, and the high mechanical strength and corrosion resistance of the steel strip are achieved.
Patent Information
- Application Number
- CN202411759767.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-03
AI Technical Summary
After the existing corrosion-resistant steel belt is bending under force or scratched on the surface, the anti-rust coating is prone to cracking, causing corrosive media to erode the steel belt body and cause material damage.
采用一种制备方法,包括配置化学镀液并施镀,随后在等离子辉光氮化炉中进行辉光等离子处理,最后通过混合合金粉末和等离子处理后粉末进行铸造和轧制,形成耐腐蚀钢带。
The prepared steel strip has good mechanical strength and corrosion resistance, and is suitable for corrosive media environments or high stress environments, improving the durability of steel components and reducing maintenance costs.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel strip manufacturing, and in particular to a corrosion-resistant steel strip and a preparation method thereof. Background Art
[0002] Corrosion-resistant steel is a low-alloy steel between ordinary steel and stainless steel. By adding a small amount of alloy elements to the steel, a dense, protective rust layer is formed on the surface of the steel material in the working environment, which prevents the corrosive medium from penetrating into the steel matrix and slows down the development of rust into the depth of the steel material, thereby improving the corrosion resistance. At present, most corrosion-resistant steels are coated with anti-rust paint or plating, but the surface plating or anti-rust layer of the steel strip is prone to cracking during the bending or surface scratching of the steel strip. The corrosive medium can easily erode the steel strip body through the cracks, causing material damage. Summary of the invention
[0003] To this end, the present invention provides a method for preparing a corrosion-resistant steel strip, the steps comprising:
[0004] (1) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, cerium dioxide powder, glycine, thiourea, sodium dodecyl sulfate and water; grinding niobium carbide powder by ball milling, and then passing through a sieve to obtain a sieved powder, soaking the sieved powder in acetone, stirring for more than 20 minutes under an ultrasonic environment, and then separating the solid from the liquid, drying the solid phase at 60° C. for more than 2 hours, soaking the dried solid phase in the chemical plating solution, heating the solid phase to 80±5° C. in a water bath for constant temperature plating for more than 60 minutes, and condensing and refluxing during the plating process; after the plating is completed, separating the solid from the liquid, washing the solid phase with deionized water for more than 3 times, and drying it at 60° C. for more than 3 hours to obtain a plated powder;
[0005] (2) placing the plated powder on a cathode plate in a plasma glow nitriding furnace, and subjecting the powder to glow plasma treatment in an environment of a mixture of hydrogen and methane, with a voltage of 700 to 750 V, a gas pressure of 400 to 450 Pa, and a treatment time of 6 to 10 h. After the treatment, the powder is cooled to room temperature in a hydrogen protective atmosphere to obtain a plasma-treated powder;
[0006] (3) mixing carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder uniformly to obtain mixed alloy powder, heating the mixed powder to 1600-1620° C. to melt into a melt, stirring with bottom argon for 20-30 min, desulfurizing, deoxidizing, and slagging, and then adding the plasma-treated powder, continuing to stir with bottom argon for 4-5 min after adding the powder, and then immediately pouring the powder into a mold for casting to obtain a cast plate;
[0007] (4) The ingot plate is heated to 1200-1280° C. and subjected to a constant temperature homogenization treatment for 100-120 min, and then roughly rolled into a strip at 1100-1160° C., and then subjected to 5-7 rounds of finish rolling to form the corrosion-resistant steel strip, with the final rolling temperature being above 950° C.
[0008] Furthermore, in the step (1), the concentrations of the components in the chemical plating solution are: nickel sulfate 25-27 g / L, sodium hypophosphite 22-24 g / L, ammonium acetate 18-20 g / L, trisodium citrate 25-26 g / L, cerium dioxide powder 1-2 g / L, glycine 1-3 g / L, thiourea 0.4-0.5 mg / L, sodium dodecyl sulfate 0.8-1 mg / L, and the solvent is water; the mass ratio of the dried solid phase immersed in the chemical plating solution is solid phase: chemical plating solution = 1:30-50.
[0009] Furthermore, in step (2), the volume ratio of hydrogen to methane in the hydrogen and methane mixed gas is hydrogen:methane=100:0.8-1.
[0010] Furthermore, in the step (3), the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; the mixed weight ratio of carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder is carbon steel powder: Fe-Cr alloy powder: Fe-Mo alloy powder: Fe-Si alloy powder: Fe-Al alloy powder = 100: 0.7~0.8: 1~2: 0.9~1.2: 0.6~1.6.
[0011] Furthermore, in the step (3), the weight of the plasma-treated powder added is 1.2% to 1.5% of the total weight of the mixed alloy powder.
[0012] The beneficial effects of the present invention are that the steel strip prepared by the method of the present invention has good mechanical strength and corrosion resistance, is suitable for working in an environment with a certain corrosive medium or in an environment with high stress requirements, improves the durability of steel components, and reduces maintenance costs. DETAILED DESCRIPTION
[0013] The present invention will be further described below in conjunction with the embodiments.
[0014] Example 1
[0015] A method for preparing a corrosion-resistant steel strip, comprising the steps of:
[0016] (1) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, cerium dioxide powder, glycine, thiourea, sodium dodecyl sulfate and water; the concentrations of the components in the chemical plating solution are: 25 g / L nickel sulfate, 22 g / L sodium hypophosphite, 18 g / L ammonium acetate, 25 g / L trisodium citrate, 1 g / L cerium dioxide powder, 1 g / L glycine, 0.4 mg / L thiourea, 0.8 mg / L sodium dodecyl sulfate, and the solvent is water; ball milling the niobium carbide powder, and then grinding it for 2 000 mesh sieve to obtain sieved powder, the sieved powder is immersed in acetone for degreasing and cleaning, stirred for 20 minutes under ultrasonic environment, then solid-liquid separation, the solid phase is dried at 60°C for 2 hours to remove acetone, the dried solid phase is immersed in the chemical plating solution, and the mass ratio of the dried solid phase immersed in the chemical plating solution is solid phase: chemical plating solution = 1:30; water bath is heated to 80±5°C for constant temperature plating for 60 minutes, and condensation reflux is carried out during the plating process; after the plating is completed, the solid-liquid separation is carried out, the solid phase is washed with deionized water 3 times, and dried at 60°C for 3 hours to obtain plating powder;
[0017] (2) placing the plated powder on a cathode disk in a plasma glow nitriding furnace, and subjecting the powder to glow plasma treatment in an environment of a hydrogen and methane mixed gas, wherein the volume ratio of hydrogen to methane in the hydrogen and methane mixed gas is hydrogen: methane = 100:0.8; the voltage is 750 V, the gas pressure is 400 Pa, and the treatment time is 6 h. After the treatment is completed, the powder is cooled to room temperature in a hydrogen protective atmosphere with the furnace to obtain a plasma-treated powder;
[0018] (3) Carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder are uniformly mixed to obtain a mixed alloy powder, wherein the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; the carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder The weight ratio of the mixed powder and the Fe-Al alloy powder is carbon steel powder: Fe-Cr alloy powder: Fe-Mo alloy powder: Fe-Si alloy powder: Fe-Al alloy powder = 100: 0.7: 1: 0.9: 0.6; the mixed powder is heated to 1610° C. and melted into a melt, bottom-blown argon is stirred for 20 minutes, desulfurized, deoxidized, and slag is removed, and then the plasma-treated powder is added, and the weight of the plasma-treated powder added is 1.2% of the total weight of the mixed alloy powder; after adding the materials, the bottom-blown argon is continued to be stirred for 4 minutes, and then immediately poured into a mold for casting to obtain a cast billet plate (with a thickness of 50 mm);
[0019] (4) The cast slab is heated to 1250° C. and subjected to a constant temperature homogenization treatment for 100 min. The cast slab is then roughly rolled into a strip at 1140° C., and then subjected to six rounds of finish rolling to form the corrosion-resistant steel strip (with a thickness of 5 mm). The final rolling temperature is 960° C.
[0020] Example 2
[0021] A method for preparing a corrosion-resistant steel strip, comprising the steps of:
[0022] (1) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, cerium dioxide powder, glycine, thiourea, sodium dodecyl sulfate and water; the concentrations of the components in the chemical plating solution are: 26 g / L nickel sulfate, 23 g / L sodium hypophosphite, 19 g / L ammonium acetate, 25 g / L trisodium citrate, 1 g / L cerium dioxide powder, 2 g / L glycine, 0.4 mg / L thiourea, 0.9 mg / L sodium dodecyl sulfate, and the solvent is water; ball milling the niobium carbide powder, and then grinding it for 2 000 mesh sieve to obtain sieved powder, the sieved powder is immersed in acetone for degreasing and cleaning, stirred for 20 minutes under ultrasonic environment, then solid-liquid separation, the solid phase is dried at 60°C for 2 hours to remove acetone, the dried solid phase is immersed in the chemical plating solution, and the mass ratio of the dried solid phase immersed in the chemical plating solution is solid phase: chemical plating solution = 1:30; water bath is heated to 80±5°C for constant temperature plating for 60 minutes, and condensation reflux is carried out during the plating process; after the plating is completed, the solid-liquid separation is carried out, the solid phase is washed with deionized water 3 times, and dried at 60°C for 3 hours to obtain plating powder;
[0023] (2) placing the plated powder on a cathode plate in a plasma glow nitriding furnace, and subjecting the powder to glow plasma treatment in an environment of a hydrogen and methane mixed gas, wherein the volume ratio of hydrogen to methane in the hydrogen and methane mixed gas is hydrogen: methane = 100:0.9; the voltage is 750 V, the gas pressure is 400 Pa, and the treatment time is 8 h. After the treatment is completed, the powder is cooled to room temperature in a hydrogen protective atmosphere with the furnace to obtain a plasma-treated powder;
[0024] (3) Carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder are uniformly mixed to obtain a mixed alloy powder, wherein the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; the carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder are uniformly mixed to obtain a mixed alloy powder, wherein the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; The powder and the Fe-Al alloy powder are mixed in a weight ratio of carbon steel powder: Fe-Cr alloy powder: Fe-Mo alloy powder: Fe-Si alloy powder: Fe-Al alloy powder = 100: 0.7: 1: 1: 0.8; the mixed powder is heated to 1610° C. and melted into a melt, bottom-blown with argon and stirred for 20 minutes, desulfurized, deoxidized, and slag-stripped, and then the plasma-treated powder is added, and the weight of the plasma-treated powder added is 1.3% of the total weight of the mixed alloy powder; after adding the materials, the bottom-blown with argon and stirred for 4 minutes, and then immediately poured into a mold for casting to obtain a cast billet plate (with a thickness of 50 mm);
[0025] (4) The cast slab is heated to 1250° C. and subjected to a constant temperature homogenization treatment for 100 min. The cast slab is then roughly rolled into a strip at 1140° C., and then subjected to six rounds of finish rolling to form the corrosion-resistant steel strip (with a thickness of 5 mm). The final rolling temperature is 960° C.
[0026] Example 3
[0027] A method for preparing a corrosion-resistant steel strip, comprising the steps of:
[0028] (1) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, cerium dioxide powder, glycine, thiourea, sodium dodecyl sulfate and water; the concentrations of the components in the chemical plating solution are: 26 g / L nickel sulfate, 23 g / L sodium hypophosphite, 19 g / L ammonium acetate, 26 g / L trisodium citrate, 2 g / L cerium dioxide powder, 2 g / L glycine, 0.5 mg / L thiourea, 0.9 mg / L sodium dodecyl sulfate, and the solvent is water; ball milling the niobium carbide powder, and then grinding it for 2 000 mesh sieve to obtain sieved powder, the sieved powder is immersed in acetone for degreasing and cleaning, stirred for 20 minutes under ultrasonic environment, then solid-liquid separation, the solid phase is dried at 60°C for 2 hours to remove acetone, the dried solid phase is immersed in the chemical plating solution, and the mass ratio of the dried solid phase immersed in the chemical plating solution is solid phase: chemical plating solution = 1:30; water bath is heated to 80±5°C for constant temperature plating for 60 minutes, and condensation reflux is carried out during the plating process; after the plating is completed, the solid-liquid separation is carried out, the solid phase is washed with deionized water 3 times, and dried at 60°C for 3 hours to obtain plating powder;
[0029] (2) placing the plated powder on a cathode plate in a plasma glow nitriding furnace, and subjecting the powder to glow plasma treatment in an environment of a hydrogen and methane mixed gas, wherein the volume ratio of hydrogen to methane in the hydrogen and methane mixed gas is hydrogen: methane = 100:0.9; the voltage is 750 V, the gas pressure is 400 Pa, and the treatment time is 8 h. After the treatment is completed, the powder is cooled to room temperature in a hydrogen protective atmosphere with the furnace to obtain a plasma-treated powder;
[0030] (3) Carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder are uniformly mixed to obtain a mixed alloy powder, wherein the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; the carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder are uniformly mixed to obtain a mixed alloy powder, wherein the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; The weight ratio of the powder and the Fe-Al alloy powder is carbon steel powder: Fe-Cr alloy powder: Fe-Mo alloy powder: Fe-Si alloy powder: Fe-Al alloy powder = 100: 0.8: 2: 1: 1.2; the mixed powder is heated to 1610° C. and melted into a melt, bottom-blown with argon and stirred for 20 minutes, desulfurized, deoxidized, and slag-stripped, and then the plasma-treated powder is added, and the weight of the plasma-treated powder added is 1.4% of the total weight of the mixed alloy powder; after adding the materials, the bottom-blown with argon and stirred for 4 minutes, and then immediately poured into a mold for casting to obtain a cast billet plate (with a thickness of 50 mm);
[0031] (4) The cast slab is heated to 1250° C. and subjected to a constant temperature homogenization treatment for 100 min. The cast slab is then roughly rolled into a strip at 1140° C., and then subjected to six rounds of finish rolling to form the corrosion-resistant steel strip (with a thickness of 5 mm). The final rolling temperature is 960° C.
[0032] Example 4
[0033] A method for preparing a corrosion-resistant steel strip, comprising the steps of:
[0034] (1) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, cerium dioxide powder, glycine, thiourea, sodium dodecyl sulfate and water; the concentrations of the components in the chemical plating solution are: 27 g / L nickel sulfate, 24 g / L sodium hypophosphite, 20 g / L ammonium acetate, 26 g / L trisodium citrate, 2 g / L cerium dioxide powder, 3 g / L glycine, 0.5 mg / L thiourea, 1 mg / L sodium dodecyl sulfate, and the solvent is water; ball milling the niobium carbide powder, and grinding it for 20 00 mesh sieve, obtain sieved powder, immerse the sieved powder in acetone for degreasing and cleaning, stir for 20 minutes under ultrasonic environment, then separate the solid and liquid, dry the solid phase at 60°C for 2 hours to remove acetone, and immerse the dried solid phase in the chemical plating solution, and the mass ratio of the dried solid phase immersed in the chemical plating solution is solid phase: chemical plating solution = 1:30; heat the water bath to 80±5°C for constant temperature plating for 60 minutes, condense and reflux during the plating process; after the plating is completed, separate the solid and liquid, wash the solid phase with deionized water 3 times, and dry it at 60°C for 3 hours to obtain plating powder;
[0035] (2) placing the plated powder on a cathode plate in a plasma glow nitriding furnace, and subjecting the powder to glow plasma treatment in an environment of a hydrogen and methane mixed gas, wherein the volume ratio of hydrogen to methane in the hydrogen and methane mixed gas is hydrogen:methane=100:1; the voltage is 750 V, the gas pressure is 400 Pa, and the treatment time is 10 h. After the treatment is completed, the powder is cooled to room temperature in a hydrogen protective atmosphere with the furnace to obtain a plasma-treated powder;
[0036] (3) Carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder are uniformly mixed to obtain a mixed alloy powder, wherein the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; the carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder The weight ratio of the mixed powder and the Fe-Al alloy powder is carbon steel powder: Fe-Cr alloy powder: Fe-Mo alloy powder: Fe-Si alloy powder: Fe-Al alloy powder = 100: 0.8: 2: 1.2: 1.6; the mixed powder is heated to 1610° C. and melted into a melt, bottom-blown argon is stirred for 20 minutes, desulfurized, deoxidized, and slag is removed, and then the plasma-treated powder is added, and the weight of the plasma-treated powder added is 1.5% of the total weight of the mixed alloy powder; after adding the materials, the bottom-blown argon is continued to be stirred for 4 minutes, and then immediately poured into a mold for casting to obtain a cast billet plate (with a thickness of 50 mm);
[0037] (4) The cast slab is heated to 1250° C. and subjected to a constant temperature homogenization treatment for 100 min. The cast slab is then roughly rolled into a strip at 1140° C., and then subjected to six rounds of finish rolling to form the corrosion-resistant steel strip (with a thickness of 5 mm). The final rolling temperature is 960° C.
[0038] Comparative Example 1
[0039] A method for preparing a steel strip for comparison comprises the following steps:
[0040] (1) The niobium carbide powder was ball-milled and passed through a 2000 mesh sieve to obtain a sieved powder, which was then soaked in acetone for degreasing and cleaning, stirred for 20 minutes under an ultrasonic environment, and then solid-liquid separation was performed, and the solid phase was dried at 60° C. for 2 hours to remove the acetone, thereby obtaining a pretreated powder of this comparative example;
[0041] (2) Carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder are uniformly mixed to obtain a mixed alloy powder, wherein the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; the carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder are uniformly mixed to obtain a mixed alloy powder, wherein the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; The weight ratio of the mixed i alloy powder and the Fe-Al alloy powder is carbon steel powder: Fe-Cr alloy powder: Fe-Mo alloy powder: Fe-Si alloy powder: Fe-Al alloy powder = 100: 0.8: 2: 1: 1.2; the mixed powder is heated to 1610° C. and melted into a melt, bottom-blown with argon and stirred for 20 minutes, desulfurized, deoxidized, and slag-stripped, and then the pre-treated powder is added, and the weight of the pre-treated powder added is 1.4% of the total weight of the mixed alloy powder; after adding the materials, the bottom-blown with argon and stirred for 4 minutes, and then immediately poured into a mold for casting to obtain a cast billet plate (with a thickness of 50 mm);
[0042] (3) The cast slab was heated to 1250° C. and subjected to a constant temperature homogenization treatment for 100 min. The slab was then roughly rolled into a strip at 1140° C., and then subjected to 6 rounds of finish rolling to obtain the corrosion-resistant steel strip (5 mm thick) described in the comparative example. The final rolling temperature was 960° C.
[0043] Comparative Example 2
[0044] A method for preparing a steel strip for comparison comprises the following steps:
[0045] (1) The niobium carbide powder was ball-milled and passed through a 2000 mesh sieve to obtain a sieved powder, which was then soaked in acetone for degreasing and cleaning, stirred for 20 minutes under an ultrasonic environment, and then solid-liquid separation was performed, and the solid phase was dried at 60° C. for 2 hours to remove the acetone, thereby obtaining a pretreated powder of this comparative example;
[0046] (2) placing the pretreated powder on a cathode plate in a plasma glow nitriding furnace, and subjecting the pretreated powder to glow plasma treatment in an environment of a hydrogen and methane mixed gas, wherein the volume ratio of hydrogen to methane in the hydrogen and methane mixed gas is hydrogen: methane = 100:0.9; the voltage is 750 V, the gas pressure is 400 Pa, and the treatment time is 8 h. After the treatment is completed, the powder is cooled to room temperature in a hydrogen protective atmosphere with the furnace to obtain the plasma-treated powder of this comparative example;
[0047] (3) Carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder are uniformly mixed to obtain a mixed alloy powder, wherein the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; the carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder are uniformly mixed to obtain a mixed alloy powder, wherein the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; The weight ratio of the powder and the Fe-Al alloy powder is carbon steel powder: Fe-Cr alloy powder: Fe-Mo alloy powder: Fe-Si alloy powder: Fe-Al alloy powder = 100: 0.8: 2: 1: 1.2; the mixed powder is heated to 1610° C. and melted into a melt, bottom-blown with argon and stirred for 20 minutes, desulfurized, deoxidized, and slag-stripped, and then the plasma-treated powder is added, and the weight of the plasma-treated powder added is 1.4% of the total weight of the mixed alloy powder; after adding the materials, the bottom-blown with argon and stirred for 4 minutes, and then immediately poured into a mold for casting to obtain a cast billet plate (with a thickness of 50 mm);
[0048] (4) The cast slab was heated to 1250°C for constant temperature homogenization treatment for 100 min, and then roughly rolled into a strip at 1140°C, and then finished rolled 6 times to obtain the corrosion-resistant steel strip (thickness 5 mm) described in the comparative example, with the final rolling temperature being 960°C.
[0049] Comparative Example 3
[0050] A method for preparing a steel strip for comparison comprises the following steps:
[0051] (1) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, cerium dioxide powder, glycine, thiourea, sodium dodecyl sulfate and water; the concentrations of the components in the chemical plating solution are: 26 g / L nickel sulfate, 23 g / L sodium hypophosphite, 19 g / L ammonium acetate, 26 g / L trisodium citrate, 2 g / L cerium dioxide powder, 2 g / L glycine, 0.5 mg / L thiourea, 0.9 mg / L sodium dodecyl sulfate, and the solvent is water; ball milling the niobium carbide powder, and then grinding it for 2 000 mesh sieve to obtain sieved powder, the sieved powder is immersed in acetone for degreasing and cleaning, stirred for 20 minutes under ultrasonic environment, then solid-liquid separation, the solid phase is dried at 60°C for 2 hours to remove acetone, the dried solid phase is immersed in the chemical plating solution, and the mass ratio of the dried solid phase immersed in the chemical plating solution is solid phase: chemical plating solution = 1:30; water bath is heated to 80±5°C for constant temperature plating for 60 minutes, and condensation reflux is carried out during the plating process; after the plating is completed, the solid-liquid separation is carried out, the solid phase is washed with deionized water 3 times, and dried at 60°C for 3 hours to obtain plating powder;
[0052] (2) Carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder are uniformly mixed to obtain a mixed alloy powder, wherein the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; the carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder are uniformly mixed to obtain a mixed alloy powder, wherein the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; The Si alloy powder and the Fe-Al alloy powder are mixed in a weight ratio of carbon steel powder: Fe-Cr alloy powder: Fe-Mo alloy powder: Fe-Si alloy powder: Fe-Al alloy powder = 100: 0.8: 2: 1: 1.2; the mixed powder is heated to 1610° C. and melted into a melt, bottom-blown with argon and stirred for 20 minutes, desulfurized, deoxidized, and slag-stripped, and then the plating powder is added, and the weight of the plating powder added is 1.4% of the total weight of the mixed alloy powder; after adding the materials, the bottom-blown with argon and stirred for 4 minutes, and then immediately poured into a mold for casting to obtain a cast billet plate (with a thickness of 50 mm);
[0053] (3) The cast slab was heated to 1250° C. and subjected to a constant temperature homogenization treatment for 100 min. The slab was then roughly rolled into a strip at 1140° C., and then subjected to 6 rounds of finish rolling to obtain the corrosion-resistant steel strip (5 mm thick) described in the comparative example. The final rolling temperature was 960° C.
[0054] Example 5
[0055] According to the requirements of standard GB / T 228.1-2021, the corrosion-resistant steel strips prepared by the methods described in each embodiment and comparative example are processed into tensile specimens with a thickness of 5 mm, and the tensile strength of each specimen is tested on a universal testing machine. The tensile rate is 0.2 mm / min, and 3 samples are tested for each group of specimens, and the average value is taken as the tensile strength value of the group. The corrosion-resistant steel strips prepared by the methods described in each embodiment and comparative example are processed into small pieces of 2 cm×2 cm×5 mm, and the small pieces are connected with wires, exposing only 1 cm×1 cm of the test surface, and the remaining surfaces are completely coated with insulating glue to make electrochemical test specimens, and then the electrochemical test specimens are subjected to polarization curve testing on an electrochemical workstation, the electrolyte solution is a 3.5wt% sodium chloride aqueous solution, the platinum electrode is the auxiliary electrode, and the saturated calomel electrode is the reference electrode, and the self-corrosion potential is obtained, and the results are shown in Table 1.
[0056] As can be seen from Table 1, the steel strip prepared by the method of the present invention has good mechanical strength and corrosion resistance, is suitable for working in an environment with a certain corrosive medium or in an environment with high stress requirements, improves the durability of steel components, and reduces maintenance costs. By comparing Example 3 of the present invention and each comparative example, it can be seen that by adding the plasma-treated powder described in the present invention, the tensile strength of the steel can be effectively improved, and the positive shift of the self-corrosion potential can be promoted to a certain extent, thereby improving the corrosion resistance. This is mainly because after adding the plasma-treated powder described in the present invention, the plasma-treated powder acts as a non-uniform nucleation point during the casting cooling process of the steel, thereby improving the nucleation rate of the steel, and the plasma-treated powder is pinned in the steel matrix grains as a second phase particle, which can effectively prevent dislocation movement during the deformation process, and play a second phase strengthening effect, thereby improving the tensile strength. On the other hand, a corrosion-resistant cerium oxide-nickel composite coating is formed on the surface of the second phase particles by the plating powder after plating, and the compatibility of nickel and iron is used to improve the interface bonding between the second phase particles and the iron matrix, reduce the number of holes and defects between the interfaces, make the material more compact as a whole, reduce the possibility of interphase corrosion, thereby improving strength and corrosion resistance, and nickel itself is an austenite-forming element, and part of the nickel melts into the iron matrix in the two-phase interface area, which can make the iron in the interface area tend to form a stable austenite structure, and can also improve the corrosion resistance of the interface. As a face-centered cubic structure, the nickel coating makes it easier for the carbon formed by the ionization of methane to enter the coating during the subsequent plasma treatment process, thereby improving the strength and corrosion resistance of the coating itself.
[0057] Table 1
[0058] Experimental Group Tensile strength(MPa) Self-corrosion potential (V) Example 1 656.1 -0.755 Example 2 669.7 -0.721 Example 3 673.2 -0.703 Example 4 670.9 -0.710 Comparative Example 1 575.4 -0.886 Comparative Example 2 611.8 -0.805 Comparative Example 3 632.2 -0.798
[0059] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for preparing a corrosion-resistant steel strip, characterized in that the steps include: (1) preparing a chemical plating solution, wherein the components of the chemical plating solution are nickel sulfate, sodium hypophosphite, ammonium acetate, trisodium citrate, cerium dioxide powder, glycine, thiourea, sodium dodecyl sulfate and water; grinding niobium carbide powder by ball milling, and then passing through a sieve to obtain a sieved powder, soaking the sieved powder in acetone, stirring for more than 20 minutes under an ultrasonic environment, and then separating the solid from the liquid, drying the solid phase at 60° C. for more than 2 hours, soaking the dried solid phase in the chemical plating solution, heating the solid phase to 80±5° C. in a water bath for constant temperature plating for more than 60 minutes, and condensing and refluxing during the plating process; after the plating is completed, separating the solid from the liquid, washing the solid phase with deionized water for more than 3 times, and drying it at 60° C. for more than 3 hours to obtain a plated powder; (2) placing the plated powder on a cathode plate in a plasma glow nitriding furnace, and subjecting the powder to glow plasma treatment in an environment of a mixture of hydrogen and methane, with a voltage of 700 to 750 V, a gas pressure of 400 to 450 Pa, and a treatment time of 6 to 10 h. After the treatment, the powder is cooled to room temperature in a hydrogen protective atmosphere to obtain a plasma-treated powder; (3) mixing carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder uniformly to obtain mixed alloy powder, heating the mixed powder to 1600-1620° C. to melt into a melt, stirring with bottom argon for 20-30 min, desulfurizing, deoxidizing, and slagging, and then adding the plasma-treated powder, continuing to stir with bottom argon for 4-5 min after adding the powder, and then immediately pouring the powder into a mold for casting to obtain a cast plate; (4) The ingot plate is heated to 1200-1280° C. and subjected to a constant temperature homogenization treatment for 100-120 min, and then roughly rolled into a strip at 1100-1160° C., and then subjected to 5-7 rounds of finish rolling to form the corrosion-resistant steel strip, with the final rolling temperature being above 950° C.
2. The method for preparing a corrosion-resistant steel strip according to claim 1, characterized in that: In the step (1), the concentrations of the components in the chemical plating solution are: nickel sulfate 25-27 g / L, sodium hypophosphite 22-24 g / L, ammonium acetate 18-20 g / L, trisodium citrate 25-26 g / L, cerium dioxide powder 1-2 g / L, glycine 1-3 g / L, thiourea 0.4-0.5 mg / L, sodium dodecyl sulfate 0.8-1 mg / L, and the solvent is water; the mass ratio of the dried solid phase immersed in the chemical plating solution is solid phase: chemical plating solution = 1:30-50.
3. The method for preparing a corrosion-resistant steel strip according to claim 1, characterized in that: In the step (2), the volume ratio of hydrogen to methane in the hydrogen and methane mixed gas is hydrogen:methane=100:0.8-1.
4. The method for preparing a corrosion-resistant steel strip according to claim 1, characterized in that: In the step (3), the carbon steel powder is 20# carbon steel powder; the weight percentage of Cr in the Fe-Cr alloy powder is 60wt%; the weight percentage of Mo in the Fe-Mo alloy powder is 55wt%; the weight percentage of Si in the Fe-Si alloy powder is 75wt%; the weight percentage of Al in the Fe-Al alloy powder is 50wt%; the mixed weight ratio of carbon steel powder, Fe-Cr alloy powder, Fe-Mo alloy powder, Fe-Si alloy powder and Fe-Al alloy powder is carbon steel powder: Fe-Cr alloy powder: Fe-Mo alloy powder: Fe-Si alloy powder: Fe-Al alloy powder = 100: 0.7~0.8: 1~2: 0.9~1.2: 0.6~1.
6.
5. The method for preparing a corrosion-resistant steel strip according to claim 4, characterized in that: In the step (3), the weight of the plasma-treated powder added is 1.2% to 1.5% of the total weight of the mixed alloy powder.
Citation Information
Patent Citations
Die steel with low cost and high thermal conductivity at high temperature, and preparation method of die steel
CN111961985A
Chemical composite plating solution and preparation method thereof as well as chemical composite plating layer and preparation method thereof
CN114855151A
Formula and preparation process of alloy powder for laser cladding
CN117226088A
Method for improving strength of hot-rolled low-carbon steel
CN118755904A
Cermet thermal-sprayed powder material excellent in corrosion resistance and plasma erosion resistance and method for manufacturing the same
JP2013010986A